2019
DOI: 10.1016/j.molstruc.2019.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution in racemic solutions of N-trifluoroacetylated α-aminoalcohols

Abstract: The spontaneous resolution was observed in the racemic solution of Ntrifluoroacetylated α-aminoalcohol (TFAAA-6) in CCl4. In against other cases of the conglomerates formation, the TFAAA-6 forms highly anisometric crystalline structures (strings). Herewith, the spontaneous resolution was not observed in the racemic solution of TFAAA-5 in heptane, where the isometric precipitate was formed. The latter was also observed in the TFAAA-5 solutions in heptane with small enantiomeric excess (EE), down to 2 %. With th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The origin and potential role of chiral asymmetry in biology have attracted the attention of the research community throughout the years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Although, at the macroscopic level, nonbiological structures with a homochiral molecular basis are not known, living organisms have been engaged in a unique experiment of creating stable homochiral systems.…”
Section: Introductionmentioning
confidence: 99%
“…The origin and potential role of chiral asymmetry in biology have attracted the attention of the research community throughout the years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Although, at the macroscopic level, nonbiological structures with a homochiral molecular basis are not known, living organisms have been engaged in a unique experiment of creating stable homochiral systems.…”
Section: Introductionmentioning
confidence: 99%
“…According with the estimation of the activation energy in the de-assembling process of the aggregates as a consequence of the interaction with D-phenylalanine molecules (Schill et al, 2017;Stovbun et al, 2018;Zlenko et al, 2019a), the binding energy involved for the reported mechanism appears not strong enough (Park and Lee, 2006;Sriramulu and Valiyaveettil, 2016) for inducing a monomerization of D-PBI. The so-called "spontaneous resolution" can be proposed as a cooperative mechanism for justifying the chiral recognition of phenylalanine amino acid (Zlenko et al, 2019b). According to this fascinating theory, the separation of two enantiomers could be obtained as amplification of the initial asymmetry under the effect of some chemical compounds already present in the system (Stovbun et al, 2019).…”
Section: Disaggregation Process Of D-pbi Aqueous Solution In Presencementioning
confidence: 99%
“…The phenomenon of asymmetric chirality in living systems has recently attracted attention as one of the most urgent fundamental problems in the scientific world [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Historically, the interest of physicists in the problem of chirality is focused on a separate search for mechanisms of symmetry breaking in the main classes of biomolecules at the initial stages of biopoiesis.…”
Section: Introductionmentioning
confidence: 99%